AGROCHEMICAL BASED INFORMATION USAGE AMONG FARMERS: A PATHWAY TO SUSTAINABLE COCOA PRODUCTION IN OSUN STATE, NIGERIA - Toyin Femi OJO; Gbenga Festus KOLODEYE; Taiwo Sulaiman OLADELE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study accessed agrochemical based information usage among cocoa farmers in Nigeria with a view to determine the sustainability of information sources for an increased cocoa production in the study area. Simple random sampling was used to select 120 cocoa farmers using structured interview schedule. Results showed that farmers were in their 50s with about 12 years of formal education. Radio (mean = 2.56) ranked highest among the sources of information while about 60 percent of the respondents indicated a very high level of usage of agrochemical information in cocoa production. Results of Pearson Product Moment Correlation showed a significant relationship between farmers’ perception (r = 0.365; p≤0.01) and usage of agrochemical based information. The findings conclude that the use of mass media as the most frequently used among farmers for agrochemicals in cocoa production may be sustainable. It is therefore recommended that the use of mass media for agrochemicals usage in cocoa production should be reinforced in passing other information to cocoa farmers.